Analisis dan Perancangan Aplikasi Wisata Di Daerah Bogor Berbasis Android - Sam Ali Nurdin; Iqbal Abdurrazaq; Muhammad Arie Aldiansyah (JISA (Jurnal Informatika dan Sains), 2019)
In the present era, it is easy to fin information, but not all information obtained is valid information. Many tourists want to know about a place to visit. In addition, due to lack of promotion by the government, so many tourist attractions that have the potential to increase icnomes many people doesn’t know about the location of tourism. Bogor is the largest area attract tourists, especially local tourists. But many tourist attractions in the area of Bogor that has not been sought by the tourists. Researchers assume that it takes an applications that provide accurate information to increase tourist in Bogor, to reduce the shortage and make it easier for tourists to know information about the sights to be visited, researchers try to find a solution. "Tourist Application in Bogor Region" is used to provide information for local and foreign tourists. This becomes an opportunity for the Bogor regional government to improve services and facilities in the city, so that tourists can feel comfortable coming to visit in the city of Bogor.